2014
DOI: 10.1016/j.jmig.2014.08.345
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Age, Myoma Size, Myoma Location, and Interval Between Myomectomy and Pregnancy May Influence the Pregnancy Rate and Live Birth Rate After Myomectomy

Abstract: Objective: To investigate which clinical characteristics will influence the pregnancy rate and live birth rate after myomectomy. Subjects and Methods: Data of clinical characteristics and reproductive outcome from 471 patients who wished to conceive and who underwent abdominal or laparoscopic myomectomy in the Obstetrics and Gynecology Hospital of Fudan University from January 2008 to June 2012 were retrospectively analyzed. Results: Average age in the pregnancy group (30.0 -3.7 years) and the nonpregnancy gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…15 Conversely, a retrospective cohort study by Zhang et al analyzed the pregnancy live birth rate of 471 patients after either abdominal or laparoscopic myomectomy and reported that larger myomas (greater than 10 cm in size) may lead to earlier detection and intervention, allowing for better pregnancy outcomes. 40 In addition to size, fibroid location is a major factor influencing clinical outcome after RALM. Elements such as precise dissection and suturing is challenging when the myomas have a deep intramural component or are located posteriorly or in the lower uterine segment.…”
Section: Discussionmentioning
confidence: 99%
“…15 Conversely, a retrospective cohort study by Zhang et al analyzed the pregnancy live birth rate of 471 patients after either abdominal or laparoscopic myomectomy and reported that larger myomas (greater than 10 cm in size) may lead to earlier detection and intervention, allowing for better pregnancy outcomes. 40 In addition to size, fibroid location is a major factor influencing clinical outcome after RALM. Elements such as precise dissection and suturing is challenging when the myomas have a deep intramural component or are located posteriorly or in the lower uterine segment.…”
Section: Discussionmentioning
confidence: 99%